Hot Stamping of a B-Pillar Reinforced Panel With 7075 Aluminum Alloy and the Feasibility Study of Short-Time Aging - Liu, Yong; Li, Jiahao; Wang, Liang; Wang, Kai; Zhu, Bin; Zhang, Yisheng (Frontiers in Materials, 2021)
Hot stamping of a B-pillar reinforced panel with 7075 aluminum alloy was carried out in an industrial production line. The effect of blank holding force (BHF) on the formability of the B-pillar reinforced panel and the effect of solution heat treatment (SHT) time on the mechanical properties were studied. Additionally, the forming precisions of a formed part before and after standard aging were detected further. Finally, both standard aging and short-time aging process were carried out to investigate the feasibility of short-time aging for real parts. The stamping results demonstrated that lower BHF or no blank holding should be used during hot stamping to avoid cracking and wrinkling. The detection of forming precisions indicated that the great majority of measured points on the part were within ± 1 mm of nominal. The mechanical property testing showed that the strength of the formed parts after a short-time aging was up to more than 90% of the as-received T6 state and more than 93% of the time can be reduced if the 90% of strength can be accepted.